MARIFAT WING – LITERATURE - Bafoyev Javahir (American Journals, 2022)
This article is devoted to the life and work of Abdulhamid Sulaiman son of Cholpon, the representative of the Jadid movement, poet, writer, translator, dramatist, great writer, and how important literature is for our society through the work of Jadid.
Keywords: the perspective of the nation, national pride, specifics (figurative nature), idealism